2014
DOI: 10.1111/jfpe.12082
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Microwave‐Induced Expansion of Starch‐Based Extruded Pellets under Vacuum

Abstract: The microwave‐induced expansion of starch‐based extruded pellets under vacuum was investigated in order to understand the underlying mechanisms. Microwave power (400, 600 and 800 W), system pressure (20, 50, 100 and 190 mbar) and initial sample mass (100, 200 and 300 g) were selected as influencing factors. During processing, the surface temperature of the matrix mainly depended on the moisture content, independent of the process parameters applied. A kinetic factor τ was calculated, which accounts for the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Potato ingredients in the form of native starch or modified potato products are used to improve the structure and texture when expanding the pellet extrudates (Kraus et al, 2014). Potato extrudates, which can be obtained from potato flakes and potato grits, have a similar expansion rate, but a completely different texture.…”
Section: Introductionmentioning
confidence: 99%
“…Potato ingredients in the form of native starch or modified potato products are used to improve the structure and texture when expanding the pellet extrudates (Kraus et al, 2014). Potato extrudates, which can be obtained from potato flakes and potato grits, have a similar expansion rate, but a completely different texture.…”
Section: Introductionmentioning
confidence: 99%
“…Xi Peng et al [64], evaluated the change in a dielectric loss concerning microwave power. It was observed that at a higher microwave power range of 150 W/g-200 W/g, dielectric loss factor significantly jumped to over 0.3 even at a lower system temperature of 25 • C and remained at a steady-state up to temperature 160 • C. However, at a short microwave power range of 75 W/g to 150 W/g, the dielectric loss remained significantly low between 0.05 to 0.1 and increased when the process temperature was greater than 80 • C. In another similar study [65], microwave power's effect on the pore distribution was evaluated. The pore distribution results showed that there is a significant increase in the nucleation rate of vapor bubbles at high microwave power, which led to a significant increase in the number of pores within small areas.…”
Section: Effect Of Microwave Operating Variablesmentioning
confidence: 79%
“…This temperature corresponds to a final moisture content of the pellets of approximately 5% (Kraus et al . ). Hence, when the microwave power input is stopped, the lowest T g,mixture is 100°C.…”
Section: Resultsmentioning
confidence: 97%
“…Every microwave vacuum-drying and expansion process in this study was stopped automatically when a surface temperature >120°C of the pellets was reached. This temperature corresponds to a final moisture content of the pellets of approximately 5% (Kraus et al 2014a). Hence, when the microwave power input is stopped, the lowest Tg,mixture is 100°C.…”
Section: Bubble Growth and Shrinkagementioning
confidence: 99%
See 1 more Smart Citation